2002
DOI: 10.1055/s-2002-30138
|View full text |Cite
|
Sign up to set email alerts
|

Dopplersonographische Blutflussmessungen in uterinen und fetalen arteriellen Gefäßen als Screeninguntersuchung in der 32. - 34. Schwangerschaftswoche

Abstract: Elevated uteroplacental Doppler flow velocity waveform indices and reduced aortic blood flow velocity might be associated with a pathological birth result and an impaired neonatal status after birth in cohorts of unselected pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…68 A few studies have reported that among pregnant women, high anxiety is associated with reduced uterine, 167 fetal and umbilical blood flow and pulsatility patterns indicative of fetal hypoxia and compensatory redistribution of blood flow to the fetal brain. 168, 169 …”
Section: Biological Pathways To Parturitionmentioning
confidence: 99%
“…68 A few studies have reported that among pregnant women, high anxiety is associated with reduced uterine, 167 fetal and umbilical blood flow and pulsatility patterns indicative of fetal hypoxia and compensatory redistribution of blood flow to the fetal brain. 168, 169 …”
Section: Biological Pathways To Parturitionmentioning
confidence: 99%